2016
DOI: 10.1098/rsos.150610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple vein microjoints on the mechanical behaviour of dragonfly wings: numerical modelling

Abstract: Dragonfly wings are known as biological composites with high morphological complexity. They mainly consist of a network of rigid veins and flexible membranes, and enable insects to perform various flight manoeuvres. Although several studies have been done on the aerodynamic performance of Odonata wings and the mechanisms involved in their deformations, little is known about the influence of vein joints on the passive deformability of the wings in flight. In this article, we present the first three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Recent investigations by means of different microscopy techniques have confirmed the occurrence of the resilin in the vein joints of numerous dragonflies78910 and other insect species1112. We have shown numerically that the vein microjoints strongly contribute to the camber formation in flight by increasing the torsional flexibility of the wing5. Hence, it is plausible to hypothesize that the microjoints may have an additional functional significance by avoiding the wing failure under impact.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Recent investigations by means of different microscopy techniques have confirmed the occurrence of the resilin in the vein joints of numerous dragonflies78910 and other insect species1112. We have shown numerically that the vein microjoints strongly contribute to the camber formation in flight by increasing the torsional flexibility of the wing5. Hence, it is plausible to hypothesize that the microjoints may have an additional functional significance by avoiding the wing failure under impact.…”
supporting
confidence: 58%
“…Although several parameters influence the deformation of the wings in Odonata, considering their distribution over the wing, vein microjoints have been recognized as one of the most effective elements, in contrast to the others56. Recent investigations by means of different microscopy techniques have confirmed the occurrence of the resilin in the vein joints of numerous dragonflies78910 and other insect species1112.…”
mentioning
confidence: 99%
“…The results obtained from tensile tests on insect wings suggested that the mechanical behaviour of insect cuticle up to fracture can be approximated by a linear elastic material model [22]. Our previous numerical studies have also demonstrated the validity of such an assumption [32,33,[37][38][39][40]. However, consideration of material plasticity is expected to have a crucial role in the realistic prediction of the stress state in insect cuticle subjected to the localized forces due to indentation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of the geometry or modulus is an effective method to understand their functions only when the effect of the manipulation on flight performance is appropriately evaluated in detail. The hind wings are always passively deformed to control wing deformations, which can affect the flight performance during flight (Rajabi et al, 2016; Jongerius and Lentink, 2010; Kesel et al, 1998; Mountcastle and Daniel, 2009), so the hind wings has higher flexibility during wind.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical and flight performances are related to the microstructures of insect wings (Wang et al, 2017; Gorb, 1999). Insects can control their wings via active and passive deformations that result in a flexible flight performance (Rajabi et al, 2016; Jongerius and Lentink, 2010; Kesel et al, 1998; Mountcastle and Daniel, 2009). The timely deformations of wings can lead to high lift and improve the distribution of aerodynamic forces on the wing during flight (Hou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%